REACTIONS OF METHOXY-SUBSTITUTED AROMATIC COAL MODELS IN SUPERCRITICAL SOLVENTS - PEHLIVAN, D; OLCAY, A (Marcel Dekker Inc, 1994)
Reactions of alpha- and beta-methoxy naphthalene and anisole in supercritical benzene and toluene were studied at 420-degrees-C and 3.9-4.4 MPa pressure. The decomposition of these lower rank coal related model compounds in both solvents was found to obey the first order rate law. While naphthols were present in the reaction mixture of methoxy naphthalenes, phenol and cresoles were present in that of anisole. In addition to these products, diphenyl or dibenzyl was also present in the reaction mixture of supercritical benzene or toluene, respectively. The reactions between models and solvents might be explained by free radical and intermolecular rearrangement reaction pathways.
Keywords: Benzyl Phenyl Ether